CSI Literacy: The Forensic Application of Basic Skills Testing - Ralf St. Clair (Adult Education Research Conference, 2010)
This presentation is a reflection on the application of literacy testing in a criminal case in the UK. A woman of retirement age was charged with fraud on the basis of a repeated false statement on a benefit form. The author was asked by defense lawyers to provide an expert opinion on whether the defendant’s claim to have misunderstood the question due to limited literacy skills was credible. The presentation reviews the procedures developed by the author to come to an informed opinion, and discusses some of the limits of literacy testing the process revealed.